2010
DOI: 10.1179/026708309x12454008169500
|View full text |Cite
|
Sign up to set email alerts
|

Tin induced crystallisation of hydrogenated amorphous silicon thin films

Abstract: The present article focuses on the effect of annealing temperatures about the Sn induced crystallisation of hydrogenated amorphous Si (a-Si:H) thin films, which are used to fabricate polycrystalline Si (poly-Si) film. The a-Si:H thin films are coated onto Sn metal thin film and subsequently annealed from various temperatures. These are crystallised by annealing for 1 h at 300°C and identified by XRD spectroscopy for the investigation of each phase. Process temperature for crystallisation should not be high bec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 15 publications
2
20
0
Order By: Relevance
“…Evidently, the onset of crystallization of a-Si occurs at 300°C by contacting with the Sn metal. Jeon et al have also reported Sn-induced crystallization of a-Si at 300°C [12]. Significantly, there is no evidence for the formation of silicides in the Sn-Si system even after annealing at 500°C.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…Evidently, the onset of crystallization of a-Si occurs at 300°C by contacting with the Sn metal. Jeon et al have also reported Sn-induced crystallization of a-Si at 300°C [12]. Significantly, there is no evidence for the formation of silicides in the Sn-Si system even after annealing at 500°C.…”
Section: Resultsmentioning
confidence: 93%
“…In contrast to these metals, Sn forms an eutectic alloy with Si with a relatively low eutectic temperature of 232°C. However, not much work has been reported on Sn-induced crystallization of a-Si films [12]. Hence, in the present work, the growth of Sn-Si nanocomposite thin films by Sn MIC of a-Si thin films is reported.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…One of the promising ways in this direction is the application of the phenomenon of metal-induced crystallization (MIC) of amorphous silicon (a-Si) [13][14][15][16][17]. In particular, a possibility to form Si nanocrystals 2-7 nm in dimensions and with a phase volume fraction of up to 80% in the a-Si matrix with the help of the low-temperature tin-induced Si crystallization was demonstrated in [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…One of promising ways in this direction is the use of metal-induced crystallization (MIC) of amorphous silicon [13][14][15][16][17]. In particular, the possibility to form Si nanocrystals in amorphous Si matrix at 2 to 5 nm sizes and the phase volume fraction up to 80% was shown by means of tin-stimulated crystallization of amorphous Si at low temperatures [18][19][20].…”
Section: Introductionmentioning
confidence: 99%